2023
DOI: 10.3389/fneur.2022.1101524
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics as a potential tool for monitoring patients with aneurysmal subarachnoid hemorrhage

Abstract: Metabolomics has evolved into a particularly useful tool to study interactions between metabolites and serves as an aid in unraveling the complexity of entire metabolomes. Nonetheless, it is increasingly viewed as a methodology with practical applications in the clinical setting, where identifying and quantifying biomarkers of interest could prove useful for diagnostics. Starting from a concise overview of the most prominent analytical techniques employed in metabolomics, herein we present a review of its appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…This initial pathogenic factor leads to secondary brain injury and the associated metabolic changes after SAH (Chen et al 2022 ). Therefore, metabolomic alterations after SAH may elucidate the pathophysiological processes that occur after SAH, and studies targeting metabolites after SAH may provide new approaches for treating secondary brain injury after SAH (Lasica et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…This initial pathogenic factor leads to secondary brain injury and the associated metabolic changes after SAH (Chen et al 2022 ). Therefore, metabolomic alterations after SAH may elucidate the pathophysiological processes that occur after SAH, and studies targeting metabolites after SAH may provide new approaches for treating secondary brain injury after SAH (Lasica et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The current review showed that metabolomics well describes the biochemical changes in post-hemorrhage CSF, with the ability to detect ischemic markers such as lactate, pyruvate, glucose, and glutamate (Ho et al 2023 ). Detection of changes in energy-supplying molecules in CSF after SAH can visualize the suffering of neural and glial cell damage and strongly suggest a prognosis (Lasica et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%